Pteridines CVII* Synthesis of 6-Azidomethyl-5,6,7,8-tetrahydropterin. Photo degradation Products and Cofactor Properties on Aromatic Amino Acid Monooxygenases - Heizmann Gerhard; Groehn Viola; Almås Bjørg; Haavik Jan; Flatmark Torgeir; Pfleiderer Wolfgang (Pteridines, 1995)
The synthesis of 6-azidomethyl-5,6,7,8-tetrahydropterin (6-AzmH4Ptr) (9) starting from 2,4-diamino- 6-hydroxymethylpteridine (1) is described. A special protecting group strategy had to be applied to perform the structural modifications. The introduction of the azido function was achieved by a Mitsunobu reaction converting the N2 - N ,N -dimethylaminomethylen-6 -hydroxymethyl-5-pivaloyl-5,6,7 ,8-tetrahydropterin (7) with diphenylphosphoryl azide into the corresponding 6-azidomethyl derivative (8). The newly synthesized compounds have been characterized by elemental analyses, UV, IR and 1H-NMR spectra. The photolysis of 6-AzmH4Ptr (9) and its inactivation effect upon aromatic amino acid mono oxygenases has been studied